Zoonotic parasites infecting free-living armadillos from Brazil - Kluyber, Danilo; Desbiez, Arnaud L. J.; Attias, Nina; Massocato, Gabriel F.; Gennari, Solange M.; Soares, Herbert S.; Bagagli, Eduardo [UNESP]; Bosco, Sandra M. G. [UNESP]; Garcés, Hans G. [UNESP]; Ferreira, Jessica da S.; Fontes, Amanda N.B; Suffys, Philip N.; et al. (Hindawi, 2021)
Armadillos are specialist diggers and their burrows are used to find food, seek shelter and protect their pups. These burrows can also be shared with dozens of vertebrate and invertebrate species and; consequently, their parasites including the zoonotics. The aim of this study was to diagnose the presence of zoonotic parasites in four wild-caught armadillo species from two different Brazilian ecosystems, the Cerrado (Brazilian savanna) and the Pantanal (wetland). The investigated parasites and their correspondent diseases were: Toxoplasma gondii (toxoplasmosis), Trypanosoma cruzi (Chagas disease), Leishmania spp., (leishmaniasis), Paracoccidioides brasiliensis (Paracoccidioidomicosis) and Mycobacterium leprae (Hansen's disease). Forty-three free-living armadillos from Pantanal and seven road-killed armadillos from the Cerrado were sampled. Trypanosoma cruzi DTU TcIII were isolated from 2 out of 43 (4.65%) armadillos, including one of them also infected with Trypanosoma rangeli. Antibodies anti-T. gondii were detected in 13 out of 43 (30.2%) armadillos. All seven armadillos from Cerrado tested positive for P. brasiliensis DNA, in the lungs, spleen, liver fragments. Also, by molecular analysis, all 43 individuals were negative for M. leprae and Leishmania spp. Armadillos were infected by T. cruzi, T. rangeli, P. brasiliensis and presented seric antibodies to T. gondii, highlighting the importance of those armadillos could have in the epidemiology of zoonotic parasites.
Keywords: Cingulata; Leishmania sp.; Mycobacterium leprae; Paracoccidioides brasiliensis; Toxoplasma gondii; Trypanosoma cruzi